Workshop Kreatif Karakter Wayang Material Limbah Sebagai Media Pengenalan Seni Tradisi Untuk Siswa Sd Negeri VI Mojosongo Surakarta - Subandi Subandi; Basnendar Herry Prilosadoso; Rahel Olivia Chandra (Institut Seni Indonesia Surakarta, 2022)
Wayang has a lengthy history in Indonesia, with each part of the archipelago having its own distinctive development and legends. Until today, wayang has remained a typical feature of each region’s culture. The phenomena of extremely strong globalization current flow today, where in the increasingly fragile state of the nation’s morals with the emergence of hedonistic and individualistic cultures, impacted life among the younger generation. The fading awareness of moral principles passed down through centuries run by ancestors has begun to be altered by norms and rules from the west, which do not correspond to the conditions of the original society. One of the solutions to counteract or reduce the foreign culture is through cultural arts. This activity serves as the effort to preserve traditional art, especially wayang and as a medium of character education for elementary school students. The implementation of activities is at a public elementary school, SD Negeri Mojosongo VI Surakarta. The method in carrying out this introductory activity prioritizes participants and mentors activeness, supported by the use of media and effective and efficient training models with the aim that training materials being well-accepted by the trainees, the elementary school students. In accordance with this, the design for this creative workshop refers to David Gibson’s concept of designing phases divided into three broad groups: planning, design, and implementation. Meanwhile, the stages of activity implementation involve three approaches: mutual, personal, and collaboration. This Paper Waste Wayang is neatly packaged to support the kids in creatively playing while learning; also, this activity contributes to the wayang preservation.